Mode of action and efficacy of iprodione against the root‐knot nematode Meloidogyne incognita. (18th October 2017) - d'Errico, G.; Giacometti, R.; Roversi, P. F.; d'Errico, F. P.; Woo, S. L.
Abstract: The ban and restriction on the use of several synthetic chemicals for controlling plant parasitic nematodes, and concern about their side effects necessitate the availability of effective methods of control with low toxicity to humans and non‐target organisms. Therefore, efficacy and mode of action of iprodione, a dicarboximide fungicide, was evaluated against the root‐knot nematode Meloidogyne incognita, in vitro and in vivo conditions, in comparison with the nematicides fenamiphos, fosthiazate and oxamyl at 7.00, 1.66 and 1.66 mL/5 L water, respectively. In vitro, iprodione showed nematostatic rather than nematicidal activity against second‐stage juveniles of M. incognita in contrast to fenamiphos, fosthiazate and oxamyl which were nematicidal. In the in vivo experiment with tomato, iprodione controlled M. incognita less than fenamiphos, fosthiazate and oxamyl. No visual symptoms of phytotoxicity were observed. Therefore, iprodione can be a useful chemical for controlling nematode populations if included in an Integrated Pest Management program. Abstract : Progressively, the chemicals used for controlling root‐knot nematodes are being banned or restricted for use. This necessitates alternative effective methods of control with low toxicity. The efficacy and mode of action of iprodione, a dicarboximide fungicide, was evaluated against Meloidogyne incognita, in vitro and in vivo conditions, in comparison with fenamiphos, fosthiazate and oxamyl. In vitro, iprodione showed mainly a nematistatic activity against second‐stage juveniles of M. incognita . Although iprodione controlled M. incognita less than chemical controls in in vivo experiment with tomato plants, it can be a useful less toxic product for controlling nematodes in Integrated Pest Management programs.